Hudson Bay, or, Everyday life in the wilds of North America [electronic resource] : during six years' residence in the territories of the Hon. Hudson Bay Company - Ballantyne, R. M. (Robert Michael), 1825-1894 (London; New York : T. Nelson, 1879)
Electronic reproduction. Mode of access: Internet. 44